Disclosing students’ challenges during digital storytelling class: A case study in higher education in Indonesia - Andriani, Agis; Fatimah, Asri Siti; Irsalina, Siti (Universitas PGRI Madiun, 2024)
Researchers and practitioners are exploring the possibilities of digital media and technology for teaching and learning because of its accessibility and progress. However, it is important to fit the users’ needs and express their identities in learning with and through them transcends hardware limitations (and intended purpose), because it became fun as a result of the allure and effectiveness of technology in piquing and maintaining interest. This study disclosed students’ challenges in creating digital storytelling and the students’ way of coping with the challenges during digital storytelling class. Three EFL students studied with digital stories in higher education were involved in semi-structured interviews.This study revealed based on thematic analysis that in creating digital storytelling during digital storytelling class, they faced working with technology, steps in creating digital storytelling takes a lot of time and creativity challenges. To overcome these they ruled the strategies that they do in coping with the challenges including improving technological skill, improving time management, and improving creativity. Further research are recommended to focus on the effectiveness about it for the students’ motivation in learning EFL.